Irish autonomous verbs in a semantic-pragmatic interface: Some reflections on information structure-driven valency reduction - Masia, Viviana (Linguistik Online, 2024)
Autonomous verbs in Irish are special verb forms incompatible with the surface realization of a subject. Previous studies have suggested to postulate empty categories such as pro, PRO or expletive pro to fill the subject position (cf. Stenson 1989; McCloskey 2007; Bondaruk/ Charzyńska-Wóicjk 2003), thus rejecting the idea that these verbs might be classified as completely subjectless. A series of syntactic tests bear out the hypothesis that, at least for Irish, these verbs behave as actually lacking a subject. I first suggest correlating this state of affairs to the fact that, with autonomous verbs, no argument role to be promoted to subject position is selected at the valency level, although it is “implied” in the unfolding of the event. Secondly, I argue that both valency reduction and syntactic non-realization of an argument role is driven by information structural constraints; notably, the focal nature of autonomous verbs (as advocated elsewhere, cf. Nolan 2012) causes the subject (together with the argument role it is associated with) to be informationally downgraded, thereby leading to its suppression in the sentence. The position held in this paper is that autonomous verbs of the Irish type epitomize an interesting phenomenon of semantic-pragmatic interface, with the pragmatic level of the utterance “mediating” between the semantic and the syntactic level; in such a perspective, the pragmatic (information structural) level of an utterance would determine either the number and type of argument roles a verb can take in a particular discourse context (cf. DuBois 1987; Goldberg 2006) and their syntactic encoding.